Surveillance of Immunological Status after Vaccination by two Serological Assays based on SARS-CoV-2 Spike Protein. (March 2022) - Fresco-Taboada, A.; Garcia-Duran, M.; Aira, C.; López, L.; Sastre, P.; Van der Hoek, L.; Van Gils, M.; Brouwer, P.J.M.; Sanders, R.W.; Holzer, B.; Zimpernik, I.; López-Collazo, E.; et al.
Abstract : Purpose: Two serological assays, an Enzyme-Linked Immunosorbent Assay (ELISA) and a Lateral Flow Assay (LFA), have been developed based on the SARS-CoV-2 recombinant Receptor Binding Domain (RBD-ELISA) and the combination of Trimeric Spike (S) and Nucleoprotein (N), S-LFA and N-LFA, respectively, as candidate tools for both indirect measurement of virus circulation and assessment of infection and vaccine-induced immunity. Methods & Materials: A total of 1272 human serum samples collected from volunteers (SARS-CoV-2 infected, non-infected or vaccinated) were evaluated by the two assays. For the RBD-ELISA, plates were coated with RBD, sera were added at 1/5 dilution and bound antibodies were detected with RBD labelled with Horseradish Peroxidase. For the LFA, two parallel strips were used: one for detection of N-specific antibodies (Hoste A. el al, 2020); and another one for detection of S-specific antibodies, using S both as capture and detector reagent. Twenty microliters of blood or ten microliters of serum were applied to each cassette and results were interpreted after ten minutes. A seroneutralization assay was used as reference for the detection of neutralizing antibodies with RBD-ELISA and Reference sera (World Health Organization), for determination of the Limit of detection (LoD). MedCalc® 10 software was used for statistical analysis. Results: The potential diagnostic application with sera from naturally infected and non-infected volunteers showed sensitivity, specificity and agreement (kappa) values of 95.1%, 99.0% and 0.94 respectively for RBD-ELISA; while 97.2%, 99.3% and 0.967 respectively for N-LFA; or 93.2% 98.3 %, 0.923, respectively for S-LFA. Serum samples from vaccinated individuals were analyzed for the specific detection of antibodies to the S protein: for vaccinated but non-infected individuals, sensitivity reached 97.3% after 15 days post-second vaccination dose whereas for previously infected people reached 100% after only 15 days post-first dose. The performance of RBD-ELISA showed good agreement with seroneutralization and excellent agreement with S-LFA (kappa 0.979). Conclusion: The dual N/S LFA represents a valuable tool to detect SARS-CoV-2 infection due to its complementary information on N and S-specific antibody response. Furthermore, the S-LFA and RBD-ELISA are both proven to be able to determine the extent of antibody response after vaccination.